Development and Validation of High Performance Liquid Chromatographic Method for Determination of Lamivudine from Pharmaceutical Preparation - S. K. Patro; S. R. Swain; V. J. Patro; N. S. K. Choudhury (E-Journal of Chemistry)
A new, simple, specific, accurate and precise RP-HPLC method was developed for determination of lamivudine in pure and tablet formulations. A Thermo BDS C18 column in isocratic mode, with a mobile phase consisting of 0.01 M ammonium dihydrogen orthophosphate buffer adjusted to pH 2.48 by using formic acid and methanol in the ratio of 50:50 was used. The flow rate was set at 0.6 mL/min and UV detection was carried out at 264 nm. The retention time of lamivudine and nevirapine were 2.825 min and 4.958 min respectively. The method was validated for linearity, precision, robustness and recovery. Linearity for lamivudine was found in the range of 50-175 μg/mL. Hence, it can be applied for routine quality control of lamivudine in bulk and pharmaceutical formulations.